Analysis of the Comparative Advantage in World Biofuel Production (2022)
Over the years, the population's need for energy has caused environmental pollution problems associated with the use of fossil fuels. Bioenergy is an alternative which various countries have proposed to reduce the volume of polluting gases into the atmosphere, with biodiésel and bioethanol being the ones that present the greatest commercial advantages worldwide, in addition to the fact that they are necessary for compliance with international agreements on environmental matters. This work focuses on analyzing the comparative advantage in 56 countries with respect to the production of biodiésel and bioethanol, for which the Revealed Comparative Advantage (VCR) and the Normalized Revealed Comparative Advantage (VCRN) index were used. The results show that to produce biodiésel, the countries with the greatest advantage are Spain, Argentina, Brazil, Indonesia and the European Union (a group of 28 countries), meanwhile for the production of bioethanol, Colombia, the United States, Argentina, Brazil and the European Union are the ones with the greatest advantages.  JEL Codes: Q24, E23 Received: 29/12/2021.  Accepted: 21/07/2022.  Published: 01/12/2022.